2018
DOI: 10.1016/j.brainres.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic dysfunction and altered excitability in C9ORF72 ALS/FTD

Abstract: Amyotrophic lateral sclerosis (ALS) is characterized by a progressive degeneration of upper and lower motor neurons, resulting in fatal paralysis due to denervation of the muscle. Due to genetic, pathological and symptomatic overlap, ALS is now considered a spectrum disease together with frontotemporal dementia (FTD), the second most common cause of dementia in individuals under the age of 65. Interestingly, in both diseases, there is a large prevalence of RNA binding proteins (RBPs) that are mutated and consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 209 publications
3
55
0
Order By: Relevance
“…We examined the role of glutamate receptors in increasing non-AUG-dependent translation following excitotoxic stress by measuring DPR levels in the presence of glutamate receptor agonists and/or antagonists. Previous work has shown that neurons derived from C9orf72 NRE patient iPS cells show increased glutamate receptors (Shi et al, 2018), age-dependent glutamate sensitivity, and hyperactivity/hypoactivity (Donnelly et al, 2013;Sareen et al, 2013;Wainger et al, 2014;Devlin et al, 2015), and motor neuron excitotoxicity may be a primary mechanism that contributes to ALS disease pathogenesis (Starr & Sattler, 2018). Furthermore, HC levels increase moderately with age in the central nervous system, and ▸ Figure 2.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…We examined the role of glutamate receptors in increasing non-AUG-dependent translation following excitotoxic stress by measuring DPR levels in the presence of glutamate receptor agonists and/or antagonists. Previous work has shown that neurons derived from C9orf72 NRE patient iPS cells show increased glutamate receptors (Shi et al, 2018), age-dependent glutamate sensitivity, and hyperactivity/hypoactivity (Donnelly et al, 2013;Sareen et al, 2013;Wainger et al, 2014;Devlin et al, 2015), and motor neuron excitotoxicity may be a primary mechanism that contributes to ALS disease pathogenesis (Starr & Sattler, 2018). Furthermore, HC levels increase moderately with age in the central nervous system, and ▸ Figure 2.…”
Section: Resultsmentioning
confidence: 93%
“…Previous work has shown that neurons derived from C9orf72 NRE patient iPS cells show increased glutamate receptors (Shi et al, 2018), age-dependent glutamate sensitivity, and hyperactivity/hypoactivity (Donnelly et al, 2013;Sareen et al, 2013;Wainger et al, 2014;Devlin et al, 2015), and motor neuron excitotoxicity may be a primary mechanism that contributes to ALS disease pathogenesis (Starr & Sattler, 2018). Previous work has shown that neurons derived from C9orf72 NRE patient iPS cells show increased glutamate receptors (Shi et al, 2018), age-dependent glutamate sensitivity, and hyperactivity/hypoactivity (Donnelly et al, 2013;Sareen et al, 2013;Wainger et al, 2014;Devlin et al, 2015), and motor neuron excitotoxicity may be a primary mechanism that contributes to ALS disease pathogenesis (Starr & Sattler, 2018).…”
Section: Glutamate-induced Increase In C9orf72 Nre Non-aug-dependent mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, elevated levels of glutamate were detected in biological samples from ALS patients 5,49,50 . Cell death caused by glutamate and calcium dysregulation has also been documented in multiple animal and cellular models 1,2 ,5- 7,51 . The outcomes of this study shed new light on the excitotoxicity cascade and implicate, for the first time, a role for the ALS/FTD-linked protein FUS in this process.…”
Section: Discussionmentioning
confidence: 99%
“…8). In ALS, this process could be compromised as a result of dysregulated Gria2 editing and/or GluR2 expression 8,53 , particularly in motor neurons that rely heavily on AMPA receptor signaling 1,2 . The effect of FUS on dendritic Gria2 density following Glu excito (Fig.…”
Section: Discussionmentioning
confidence: 99%